Experimental Investigation of Surface Ignition Using Ethanol in Di-Disel Engine - Balaji R, M Kannan, M.Arhun Jaya Sai, M V S S D Rajeswara Rao, B.Gokul (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In present scenario, a rapid increase in usage of automobiles for transportation and the depletion of fossil fuel had forced researchers to find suitable alternative fuels to be used in Internal Combustion (IC) engines. The paradox of soot-NOx is an incredibly difficult unsolved problem in compression ignition engines. One of the most viable alternatives for combustion combining the advantages of SI and CI modes, Homogeneous Load Compression Ignition (HCCI). Similar to compression ignition engines, it gives high heat efficiency and resolves the associated problems of high NOx and PM levels at the same time. The homogeneous mixture of air and fuel spontaneously burns in the combustion chamber in the HCCI combustion cycle, minimizing the overall burning time due to a high heat release rate. In this experiment ethanol was used as sole fuel in conventional CI engine by inserting a glow plug in the engine. It was performed on unmodified constant speed single cylinder direct injection diesel engine and based on the results brake thermal efficiency at the maximumload is 23.85% for ethanol, that of diesel is 27.3%, respectively, that is lower for ethanol as fuel. The reduction in the efficiency is due to the lower heating value and inferior combustion of ethanol. Thus, This Paper outcomes draw on effective utilization of ethanol with diesel and also in the aspects of economy effective.